MINAT BERWIRAUSAHA PADA WANITA DI KOTA BENGKULU - Afriani, Sulisti; Yanti, Rina Trisna; Ellya, Ellya (ITB AAS Indonesia Surakarta, 2024)
You don't have to be a man to open a business, this can also be done by women. With various factors behind this. The aim of this research is to determine women's interest in business, especially the factors that are behind it. This research used 31 women who opened businesses, the data collection method used a questionnaire distributed using Google Form. The analysis method used is frequency distribution. From the research results, it is known that the factors that encourage women's interest in opening a business are several factors which include: the presence of opportunity and opportunity at 38.7%, trying to improve their abilities 25.8%, wanting to open up employment opportunities (16.1%) the desire to organize own finances, having flexible time each has the same value of 9.7%. And the background for them opening their own business is: (1) helping to increase family income by 45.2%, factors to be independent 25.8%, developing hobbies 25.6%, compulsion to be the backbone of the family and side business only 1 .3% and side businesses alone 1.4%. Keywords : interest, entrepreneurship,women.